Penatalaksanaan klinis tumor gastrointestinal pada seekor anjing rottweiler - Prieske Tannya; Nyimas Syifa Amira Isnaini; Hasnah Tarisa; Sadhira Parameshtya; Siti Nursaumawati; Srivaen Vadivellan; Deny Setyo Wibowo; Rini Madyastuti Purwono (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Gastrointestinal neoplasia is an increasingly recognized condition in dogs, particularly in predisposed breeds, such as Rottweilers. A 4-year-old Rottweiler was presented by its owner to the Veterinary Teaching Hospital, School of Veterinary Medicine and Biomedical Sciences, IPB University, with clinical signs including coughing, dyspnea, lethargy, and intermittent yellow-brown, malodorous feces. Diagnostic evaluations revealed significant abnormalities in the respiratory and gastrointestinal systems. This report describes the clinical presentation, diagnostic approach, and management of a dog with suspected gastrointestinal neoplasia. The patient was provisionally diagnosed with gastrointestinal neoplasia with a poor prognosis. Although surgical intervention is generally recommended, the compromised pulmonary function of the dog precluded general anesthesia; therefore, management was limited to symptomatic and supportive therapy.